The Role of Financial Performance in Mediating The Effect of Good Corporate Governance on Financial Distress - Ratieh Widhiastuti; Ahmad Nurkhin; Nurdian Susilowati (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2019)
AbstractThis research aims to study the effect of good corporate governance on financial distress directly and mediated by financial performance. The study population was a manufacturing company listed on the Indonesia Stock Exchange (IDX) in 2016. The study sample was determined using the purposive sampling method, which produced 137 companies that met the requirements. The research data uses secondary data in the form of financial statements and annual reports of manufacturing companies obtained through the Indonesia Stock Exchange website. The analytical tool to test the research hypothesis is Analysis of Moment Structures (AMOS). The results of the study show that there is no direct and indirect impact on corporate governance to financial difficulties; while financial performance has a negative impact on financial difficulties. Keywords: Financial Performance, Good Corporate Governance, Financial DistressPeran Financial Performance dalam Memediasi Pengaruh Good Corporate Governance Terhadap Financial DistressAbstrakTujuan penelitian ini adalah untuk mengetahui pengaruh good corporate governance terhadap financial distress baik secara langsung maupun dengan dimediasi oleh financial performance. Populasi penelitian adalah perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia (BEI) pada tahun 2016. Sampel penelitian ditentukan dengan menggunakan metode purposive sampling, yang menghasilkan 137 perusahaan yang memenuhi syarat. Data penelitian menggunakan data sekunder berupa laporan keuangan dan annual report perusahaan manufaktur yang diperoleh melalui website Indonesia Stock Exchange. Alat analisis untuk menguji hipotesis penelitian yaitu Analysis of Moment Structures (AMOS). Hasil penelitian menunjukkan good corporate governance tidak berpengaruh baik secara langsung maupun tidak langsung terhadap financial distress; sedangkan financial performance berpengaruh negatif signifikan terhadap financial distress. Kata kunci: Financial Performance, Good Corporate Governance, Financial Distress